Incorporation of offshore shell companies as an indicator of corruption risk in the extractive industries - Giovanna Marcolongo; Diego Zambiasi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We show that the incorporation of offshore entities increases when oil and gas exploration licences are awarded. We exploit leaked data on the incorporation of shell companies and detailed information on tax havens and the awarding rounds of oil licences to construct a new data set covering 119 countries over the period 1990-2014. We consider the incorporation of offshore entities as an indicator of corruption risk. We find that the number of new shell companies increases by 11.1 per cent in the period around the award of an exploration licence. We interpret this evidence as a strong indicator that the award of an exploration licence increases the risk of corruption. Consistent with rent-maximising behaviour, this association is stronger when the price of oil increases. Our work informs the fight against corruption, proposing greater monitoring of the ultimate beneficiaries of opaque companies that participate in awarding procedures.
Keywords: D72; D73; O13; Q32; 330; oil; extractives; natural resources; corruption; tax havens; shell companies